2018
DOI: 10.2478/enr-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of ghrelin/obestatin balance with cardiometabolic risk in obese subjects with Helicobacter pylori

Abstract: It can be concluded that ghrelin, obestatin, and leptin are affected by presence of H. pylori seropositivity in obese subjects. The higher ghrelin levels and ghrelin/obestatin ratio with lowered obestatin could be considered as a gastro-protective effect against inflammation induced by H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…Similar to our findings, other studies in humans have shown that plasma obestatin levels are significantly lower in obese subjects, as compared to controls, indicating a role for obestatin in long-term body weight regulation [20,17,21].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, other studies in humans have shown that plasma obestatin levels are significantly lower in obese subjects, as compared to controls, indicating a role for obestatin in long-term body weight regulation [20,17,21].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that serum leptin levels are signi cantly reduced in patients with H. pylori infection. [28,29] Low levels of leptin delay satiety while eating, causing excessive nutrient intake and obesity. [30] Second, insulin resistance is a signi cant risk factor for metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the impact of H. pylori eradication on the metabolic response to bariatric surgery has been evaluated, showing a greater reduction in BMI at 3 months after surgery in patients treated for H. pylori ( 17 ). Previous studies have suggested that H. pylori infection may affect gastric hormones involved in appetite regulation, such as ghrelin and obestatin ( 46 ), that are mainly produced in the gastric fundus, so the relation between H. pylori infection, gastric hormones, and bariatric surgery is an issue that deserves further investigation. Indeed, the role of gastric hormones in bariatric surgery outcomes has been brought to light by a recent study that suggests a reprogramming of endocrine cell differentiation after bariatric surgery ( 47 ).…”
Section: Discussionmentioning
confidence: 99%